Multicriteria Group Decision Making by Using Trapezoidal Valued Hesitant Fuzzy Sets. (14th July 2014) - Rashid, Tabasam; Husnine, Syed Muhammad
Abstract : The concept of trapezoidal valued hesitant fuzzy set is introduced. Notion for distance between any two trapezoidal valued hesitant fuzzy elements is given. Using this proposed distance measure, we extend the technique for order preference by similarity to ideal solution for trapezoidal valued hesitant fuzzy sets. An example is constructed to show usefulness of this extension for multicriteria group decision making, where the opinions about the criteria values are expressed as trapezoidal valued hesitant fuzzy set.